Rationale for Possible Targeting of Histone Deacetylase Signaling in Cancer Diseases with a Special Reference to Pancreatic Cancer - Mehdi Ouaïssi (Journal of Biomedicine and Biotechnology, 2011)
There is ongoing interest to identify signaling pathways and genes that play a key role in carcinogenesis and the development of resistance to antitumoral drugs. Given that histone deacetylases (HDACs) interact with various partners through complex molecular mechanims leading to the control of gene expression, they have captured the attention of a large number of researchers. As a family of transcriptional corepressors, they have emerged as important regulators of cell differentiation, cell cycle progression, and apoptosis. Several HDAC inhibitors (HDACis) have been shown to efficiently protect against the growth of tumor cells in vitro as well as in vivo. The pancreatic cancer which represents one of the most aggressive cancer still suffers from inefficient therapy. Recent data, although using in vitro tumor cell cultures and in vivo chimeric mouse model, have shown that some of the HDACi do express antipancreatic tumor activity. This provides hope that some of the HDACi could be potential efficient anti-pancreatic cancer drugs. The purpose of this review is to analyze some of the current data of HDACi as possible targets of drug development and to provide some insight into the current problems with pancreatic cancer and points of interest for further study of HDACi as potential molecules for pancreatic cancer adjuvant therapy.